Pengaruh Kemiskinan dan Pengangguran terhadap Pertumbuhan Ekonomi di Provinsi Jambi Tahun 2019-2023 - Rismaya Eviara; Novi Mubryarto; G.W.I Awal Habibah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Economic growth is a factor that influences the level of poverty, considering the increasing population which means that economic needs will also increase, so additional income is needed every year. The purpose of this thesis is to determine the effect of poverty and poverty on economic growth in Jambi Province in 2019-2023. The analysis method used is the Panel Data Regression Method. The results of the study obtained that poverty has a positive and significant effect on economic growth in Jambi Province in 2019-2023, so that the hypothesis (H1) proposed by the researcher is accepted with a significance value of 0.0308 <0.05 with a t-statistic value of 2.220545. Unemployment has a positive but not significant effect on economic growth in Jambi Province in 2019-2023 in Jambi Province, so that the hypothesis (H2) proposed by the researcher is rejected with a significance value of 0.4054> 0.05 with a t-statistic value of 0.838862. Poverty (X1) and Unemployment (X2) together influence economic growth in Jambi Province in 2019-2023 in Jambi Province (Y) with a calculated F value of 2.562611 and a significant value of 0.04680 <0.05 then Ho is rejected and Ha is accepted. For this reason, the government must increase employment opportunities and the government must pay more attention to the level of poverty as well as increase economic growth. Islam hates poverty and poverty because according to Islam, economic growth, wealth is a blessing and gift from Allah SWT that must be grateful for by mankind. Poverty, poverty and economic stagnation must be eliminated so as not to endanger faith, morals and morals, even divisions in society. Increasing quality employment opportunities and reducing poverty levels are important priorities to improve the quality of life of the community and create social stability.